Reduced tolerogenic factor sCD83 in NMOSD and relapsing MOGAD: a potential new therapeutic pathway - Rechtman, Ariel; Zveik, Omri; Shweiki, Lyne; Hoichman, Garrick; Friedman-Korn, Tal; Brill, Livnat; Vaknin-Dembinsky, Adi (Frontiers in Immunology, 2025)
BackgroundNeuromyelitis optica spectrum disorders (NMOSD) and myelin oligodendrocyte glycoprotein antibody-associated disease (MOGAD) are autoimmune central nervous system disorders with poorly understood immune pathways. CD83 plays a crucial role in the development and maintenance of immune tolerance. This study aims to evaluate CD83 expression in NMOSD and MOGAD and its correlation with disease activity.MethodsRNA extracted from PBMCs of MOGAD, NMOSD and healthy controls (HCs) was analyzed to assess CD83 expression levels. ELISA was used to quantify soluble CD83 (sCD83) levels in the CSF and serum of patients. Additionally, the effects of therapeutic agents used for CNS demyelinating diseases on sCD83 expression levels were examined. The study enrolled 231 untreated participants, including 64 with MOGAD, 56 with NMOSD, 47 with MS, and 64 HCs.ResultsNMOSD patients exhibited lower sCD83 levels compared to MOGAD and HCs, and MOGAD patients with a relapsing course had lower sCD83 levels than those with a monophasic course. Lower sCD83 levels correlated with a severe disease course. Treatment with IVIG and azathioprine significantly increased sCD83 levels in the patients’ serum. In vitro treatment with immunosuppressives led to a significant increase in sCD83 levels with the most pronounced effect observed following treatment with mycophenolate mofetil.DiscussionOur study consistently found lower sCD83 levels in NMOSD and relapsing MOGAD patients. sCD83 levels increased following IVIG and immunosuppressive therapy. This elevation may reflect either a direct effect of the therapy itself, or a compensatory rebound response following immune suppression. These findings highlight the potential of sCD83 as a prognostic biomarker in these diseases and support its role as both a therapeutic target and a marker for treatment response in CNS demyelinating disorders.